"A Return to and of the Land": Indigenous Knowledge and Climate Change Initiatives across the Canadian Prairies. Issue Volume 41:Issues 3(2021) (October 2021) - Cameron, Laura; Mauro, Ian; Settee, Kevin
While research on Indigenous knowledges on climate change is increasing, especially in the Arctic, few studies document Indigenous perspectives on climate change in the Canadian Prairie provinces (Alberta, Saskatchewan, and Manitoba). This paper addresses this gap and follows an Indigenous community-based research approach using semi-structured interviews and participatory video to explore how Indigenous peoples in the Prairies are experiencing and responding to climate change. Ten video interviews were conducted with members of eight communities across the Indigenous territories of Treaties 1, 4, 6, 7, and 8. An integrated video editing and qualitative content analysis approach was conducted and eight short videos were produced. Results show that participants across diverse territories have experienced changes in their environments—attributed to the cumulative impacts of industrial development, climate change, and other influences of colonialism—which have significant impacts on cultural well-being. Communities are also pursuing solutions—such as land-based education, renewable energy, grassroots activism, cross-cultural dialogues, and ecological restoration—which serve to address these socio-ecological challenges. Across these solutions, six common themes emerged: Indigenous leadership; capacity and self-sufficiency; sustainable economic development; sharing Indigenous knowledge; connecting with the land; and bridging Indigenous knowledge and Western science. While it is increasingly recognized as critical to heed Indigenous voices on climate change, this paper makes a significant contribution to understanding the diversity and parallels in the ways in which Indigenous communities are being impacted by and responding to climate change in the Prairie provinces, as well as collaborative and creative methods for sharing these perspectives across cultures and geographies.